Experimental Studies on a Recombinant Hirudin, CGP 39393 - Gray, E; Watton, J; Cesmeli, S; Barrowcliffe, T W; Thomas, D P (Thrombosis and Haemostasis, 1991)
The in vitro anticoagulant activities of recombinant desulphatohirudin (r-hirudin) were studied in the activated partial thromboplastin time (APTT) and the thrombin generation test : systems. In the APTT at concentrations below 5 μg/ml, r-hirudin showed a dose-response curye. At concentrations above 5 μg/ml, the plasma became unclottable, but in the thrombin generation test , at least 10 μg/ml of r-hirudin was required for full inhibition of thrombin generation. The antithrombotic effect was assessed using a rabbit venous stasis model; 150 μg/ml r-hirudin completely prevented thrombus formation at 10 and 20 min stasis. At antithrombotic dose, the mean bleeding time ratio measured in a rabbit ear template model, was not prolonged over control values. At higher doses, the bleeding time ratios were higher than those observed for the same dosage of heparin. These data indicate that while r-hirudin is an effective antithrombotic agent, antithrombotic doses have to be carefully titrated to avoid excessive bleeding.